The Manifestation of Gender Peculiarities in Political Discourse - Arustamyan, Ruzanna (Armenian Folia Anglistika, 2014)
The article is devoted to the description of gender peculiarities in political discourse. The differences of male and female speeches aim to determine the degree of effectiveness of the impact of gendered approaches in political communication on male and female audiences. We may observe obvious differences between male and female speeches. It is conditioned by biological differences and social roles and stereotypes fixed in the society. Sometimes female politicians tend to imitate male speech behavior in order to defend their positions and the right to participate in the political life of their country.
Keywords: gender; political discourse; male and female languages; communicative behaviour